Implementasi Model BCC Data Envelopment Analysis (DEA) Pada Pengukuran Efisiensi Bank BUMN Tahun 2017-2021 - Indah Wulandari; Djoni Djatnika (International Forum of Researchers and Lecturers, 2023)
The study aims to find out the efficiency of BUMN bank performance in Indonesia in 2017-2021 as well as the potential improvement to inefficient bank performance. Research of this type is descriptive quantitative. The secondary data used comes from the Indonesia Financial Services Authority, each bank and the Bank of Indonesia. The sample taken using purposive sampling is taken 4 banks BUMN. Data envelopment analysis (DEA) is the technique utilized for data analysis and the program utilized is MaxDEA. A bank is considered to be efficient if it achieves an efficient value of 100%, a bank that achieves a value <100% can be said to be relatively less eficient. The results of the study showed that BRI and BTN got 4 perfect efficient DMUs. Four of BNI’s DMUs were inefficient, and just one received a perfect efficient DMUs. At the same time, Mandiri Bank has three perfect efficient DMUs and two inefficient DMUs.